Classification of Pulsar Candidates Using an Ensemble Model - Kumar Sahu, Sanat (International Journal of Computer Sciences and Engineering, 2021)
In the past, researchers study candidate filters used to solve the problem for the last years. Pulsar is a type of star, which is interested in the great scientific topic. Through which we discover this celestial pulsar. Here we have used the decision tree under the new machine learning in this research. We use two classification techniques C4.5 Tree and classification and regression tree CART to classify the HTRU2 dataset and we set a model C4.5 Tree and CART from the ensemble of the classification and regression tree. The Model Ensemble C4.5 Tree and CART provides the best performance compared to the individual models of each classifier. Ensemble Model is useful for classifying candidates in pulsar and non-pulsar.